API ADAD Colombia Trial initial findings: a randomized, double‐blind, placebo‐controlled, parallel‐ group study in cognitively unimpaired PSEN1 E280A mutation carriers evaluating efficacy and safety of crenezumab. (20th December 2022) - Sink, Kaycee M.; Doody, Rachelle S.; Ríos‐Romenets, Silvia; Tariot, Pierre N.; Reiman, Eric M.; Langbaum, Jessica B.
Abstract: The Alzheimer's Prevention Initiative (API) ADAD Colombia trial enrolled 252 cognitively unimpaired 30‐ 60‐year‐old Presenilin 1 (PSEN1) E280A mutation carriers and non‐carriers; carriers were randomized 1:1 to crenezumab or placebo, non‐carriers received placebo only. Crenezumab is an anti‐amyloid monoclonal antibody that binds beta‐amyloid (Aβ) oligomers that is hypothesized to prevent the buildup of pathogenic Aβ plaques and modify Alzheimer's disease (AD) progression with a low risk of amyloid related imaging abnormalities. The presentation will begin with a summary of the partnership between the Neurosciences Group of Antioquia and ADAD kindreds, including those who volunteered for the trial. Next will be a brief summary of the trial design and baseline participant characteristics, including the distribution of Aβ‐positive and ‐negative individuals, followed by the results for the co‐primary endpoints, change in cognitive function (using the API ADAD Cognitive Composite Test Battery) or episodic memory function (using the Free and Cued Selective Reminding Test); secondary efficacy results including time to clinical progression to MCI or dementia due to AD, time to Clinical Dementia Rating (CDR) score >0, and increase in CDR Sum of Boxes; other outcomes including FAST, NPI, MMSE, CERAD word recall and RBANS results; and safety and tolerability. Last will be a presentation of results for changes in Aβ, FDG and tau PET; volumetric brain MRI; CSF biomarkers; a preview of pending plasma biomarker data; and a brief summary of the historical context and strategic aims of API and the trial. There will be an interactive question and answer session.